Some information concerning the biography of I.V. Bugaevsky-Blagodarny - Evseeva, Ekaterina D. (Actual Problems of Theory and History of Art, 2012)
The fate and creative work of Ivan Vasilievich Bugaevsky-Blagodarny, the only one who depicted the artist Borovikovsky, had never been a target of a special research. We have reconstructed some episodes of his biography with the use of materials from ancient periodicals and archival documents. The history of his family goes back to the 17th century. It was closely connected with the Ukrainian Cossacks. Bugaevsky arrived to Petersburg in 1813, and later he made a career as a clerk, but at the same time he painted numerous portraits and icons for private commissioners. The author of this article is also mentioning the circle of customers, friends and protectors of the painter.
Keywords: biography; social status of painter; family history; clerks of St. Petersburg; private commission; minor painter